2018
DOI: 10.1016/j.cnp.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of isolated myoclonus in an elderly male without a history of epilepsy

Abstract: HighlightsWe describe a unique presentation of isolated lingual myoclonus presenting as intermittent expressive aphasia associated with uninterrupted intrusion-protrusion movement of the posterior tongue and adjoining hyoid.We discuss the paucity of evidence and suggest differential diagnosis as well as a brief discussion on possible underlying pathophysiology.Highlight previously described movement disorders and associated cases and draw parallels to isolated lingual myoclonus.Consolidate literature regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The case of our patient with orofacial myoclonus in form of persistent, rhythmic galloping movements strictly restricted to the tongue is unique. In most previous reported cases the tongue hyperkinisias were consisting of rhythmic predominantly bilateral symmetric jerking contractions or intrusion-protrusion movements [1,2] as part of myoclonus of the palatopharyngeal or orofacial muscles. Episodes of rhythmic undulating wave-form tongue movements as observed in our patient were described in only two patients after suffering head trauma [3] and in three children [4] accompanied by EEG pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of our patient with orofacial myoclonus in form of persistent, rhythmic galloping movements strictly restricted to the tongue is unique. In most previous reported cases the tongue hyperkinisias were consisting of rhythmic predominantly bilateral symmetric jerking contractions or intrusion-protrusion movements [1,2] as part of myoclonus of the palatopharyngeal or orofacial muscles. Episodes of rhythmic undulating wave-form tongue movements as observed in our patient were described in only two patients after suffering head trauma [3] and in three children [4] accompanied by EEG pathology.…”
Section: Discussionmentioning
confidence: 99%
“…An association with this pattern of extended orofacial hyperkinesia has not yet been reported. The phenomenon can extremely rarely occur in isolation without detection of an underlying pathology [1,5,[7][8][9][10]. Ong et al [11] reported a possible association based on one unique case between lingual myoclonus and neuropsychiatric lupus.…”
Section: Discussionmentioning
confidence: 99%